Grundtvig landemodetaler - Bugge, K. E. (Grundtvig-Studier, 1953)
Addresses Read by Grundtvig at Diocesan Meatings. By K. E. Bugge. The years from 1813 to 1820 were deseribed by Grundtvig as "seven Iean years", and not without reason. At that time he was regarded by his scholarly colleagues as a fanatical visionary, and among his fellow-clergy he also stood alone. An essential cause of this was the bold and provocative attitude adopted by him at the supplementary dioecesan meetings. The institution of dioecesan meetings was introduced into Denmark in 1618, and from then onwards the meetings were held twice yearly, and in later times only once yearly. Here the Bishop gatbered together the deans of the diocese to discuss matters affecting the clergy. In 1809 Bishop Munter had a regulation put into force in accordance with wich all the clergy in the diocese were invited to take part in the so-called "supplementary diocesan meeting" which took place after the regular meeting was finished. The purpose of this gathering was to hear papers read on theological subjects. Grundtvig took part in these supplementary diocesan meetings during the period when he was curate for his father, Pastor Johan Grundtvig, at Udby (1811-13) , and again a couple of times in 1814. He read a paper on each occasion. The first time was in October, 1811, when he read a paper "On Scolarship among the Clergy". The original paper , the manuscript of which has been preserved , has not yet been published; it is directed against the excessive worship of reason by the "enlightened" school of theology. Grundtvig himself , however, published a revised version of his address in 1813. - The manuscript of Grundtvigs second paper contributed to a diocesan meeting - in July, 1812 - first came to light in the autumn of 1951. It is a long essay on "Enlightenment". Grundt vig here draws a distinction between three kinds of enlightenment : the inter pretation of the word given by the Bible Christianity of his forefathers, Kant's interpretation, and finally, the most widespread type of "enlightenment", which directly breaks down everything connected with Christianity of olden times. Of this last type of enlightenment he declares: "I venture to say that the present age takes pride in its shame ... for its enlightenment consists in the pursiut of earthly things ... To be absorbed in the confusion of the earth or to rove through the empty air, that is what people eaU enlightenment". True enlightenment , on the other hand, is "that which is given from above". Grundtvigs third contribution to a diocesan meeting (in the autumn of 1812) was the wellknown "Roskilde-Riim" which he published in 1814 with many additions and alterations. The main purpose of these verses is to set forth the crushing verdict of history upon the interpretation of Christianity offered by the "enlightened" school of theology. Grundtvig's fourth address read to a diocesan meeting - in July, 1813 - has not yet been published. Accor ding to a statement by Grundtvig him self, it dealt with biblical interpretation; and in the Grundtvig arehives there are at least two essays which , in accor dance with their subject and external criteria, could be this address. Here Grundtvig attacks the methods of biblical interpretation used by the "en lightened " school of theology, which allow human reason to judge whether the sayings of the Bible are worthy of belief or not. In his fifth addre.ss to a diocesan meeting - which, unlike the others, was read at the diocesan meeting at Maribo - Grundtvig describes how we are ju stified in expecting that the Church of Christ, in spite of the present times of tribulation, will renew itself again . This essay was published in "Dansk Kirketidende", 1876, with moder nised spelling. In his sixth and last address to a diocesan meeting Grundtvig attacks one of the shibboleths of the Age of Enlightenment: tolerance. The address, which gave so much offence that the Bishop forbade Grundtvig to show himself at the diocesan meetings any more, is printed in the edition of Grundtvigs works by Hal Koch and Georg Christensen. lt is characteristic of Grundtvigs addresses to diocesan meetings that they all had a very definlte obj ect: to contend against the excessive worship of reason by the "enlightened" school of theology, "which", as he says, "like a devouring worm daily eats its way into the heart of the people." This is of fundamental importance for an understandin g of Grundtvig's educational ideas as they were expressed in his writings of the 1830's and later. Here the key word is precisely "true enlightenment". In the addresses to the diocesan mee tings we have the first violent polemics against "false enlightenment". Both in these addresses and in his later educational writings Grundtvig stresses the point that true enlightenment is the light shed upon our human life by what the Bible - not reason - has to say about the human lot.